Mechanistic study of quercetin in the treatment of thyroid cancer with diabetes based on network pharmacology and in vitro experiments - Liu, Siyu; Cai, Yujie; Chen, Wenjing; Yuan, Xiao; He, Zhipeng; Lin, Feng (Frontiers in Endocrinology, 2025)
IntroductionThyroid cancer (TC) stands as a prevalent malignancy within the global endocrine system, with its incidence notably exacerbated by the presence of diabetes. However, the specific relationship between TC and diabetes and promising treatment strategies that address both conditions simultaneously are still under exploration. Quercetin, herb medicine from traditional Chinese medicine (TCM), is widely used as an adjunctive therapy with Western medicine in the treatment of many diseases based on a wide range of biological effects. The objective of this study was to explore the efficacy of quercetin in treating TC with diabetes combining bioinformatics and network pharmacology.MethodsAfter multistep Cox proportional hazards regressions, we built a prognostic risk model for TC-diabetes and identified targets for quercetin in treating TC with diabetes. Molecular docking was employed to evaluate the binding affinities of quercetin with core targets, and in vitro experiments verified quercetin’s targets and functions.Results11 prognostic genes were included in the prediction model with a great performance in predicting the prognosis of TC-diabetic patients. 45 genes served as the targets of quercetin in treating TC with diabetes, among which, 5 core genes were screened as the most contributors. Through molecular docking, matrix metalloproteinase-3 (MMP3) was identified as the potential therapeutic target of quercetin. In vitro experiments have found that quercetin can inhibit the proliferation of thyroid cancer cells and the expression of MMP3 under high glucose conditions.DiscussionIn summary, quercetin may suppress the progression of TC-diabetes by inhibiting the proliferation of thyroid cancer cells and the expression of MMP3.